Analysis of the Deep Learning Strategies Questionnaire with Ecuadorian students - Yaguarema, Marcia; Zambrano R., Jimmy; Salavarría, Melba (Frontiers in Education, 2022)
Measurement of self-regulated learning through self-report questionnaires can help improve educational efforts. Panadero et al. (2021) validated the Deep Learning Strategies Questionnaire consisting of 30 items and four scales: basic learning self-regulation strategies, visual elaboration and summary strategies, deep information processing strategies, and self-regulated social learning strategies. We examined the characteristics of the questionnaire with 694 Ecuadorian students. The exploratory factor analysis resulted in four factors, like the original model. However, the factors identified as basic and social learning strategies included items of visual elaboration and summary and deep processing strategies. Further group comparisons showed that participants with high school finished used fewer visual and verbal elaboration strategies than those with higher education levels and that males use more deep information processing strategies than females. We discuss the difficulty of separating self-regulated learning strategies and conclude with suggestions for future research and recommendations for educational practice.